(untitled) (Indian Journal of Chemistry (IJC), 2023)
In this study, quantum chemical and spectroscopic techniques were used to investigate (E)-1-(1H-imidazol-1-yl) and (3-(1H-indol-2-yl)prop-2-en-1-one. Density functional theory simulations at the B3LYP/6-31++G(d,p) level of theory were performed to analyse the geometrical characteristics, NLO activity, and frontier molecular orbitals of synthesised substances. Frontier molecular orbitals (FMOs) analysis was done to determine the kinetic stability of the synthesised compound. The dipole moment and initial hyperpolarizabilities of the investigated compounds demonstrate their suitability as potential nonlinear optical materials. Moreover, molecular structure, vibrational assignments, 1H and 13C NMR chemical shift values were also taken and analysed for the titled compound.